IVS-II-648/649 (–T) (HBB: c.316−202del) Triggers a Novel β-Thalassemia Phenotype. (2nd January 2017) - Azimi, Azam; Alibakhshi, Reza; Hayati, Hasibeh; Tahmasebi, Soosan; Alimoradi, Sasan
Abstract: Thalassemia is the most common inherited disorder in Iran. There are approximately 800 different genomic alterations of the β-globin gene described in the HbVar database. In this study, we identified a novel mutation in a 21-year-old woman [IVS-II-648/649 (–T); HBB : c.316−202del)] and describe its clinical implications. Two other members of this family, all with hematological and clinical features associated with β-thalassemia (β-thal), also carried this mutation. The molecular diagnosis of the β-globin gene mutation was performed by direct sequencing. Based on the observed β-thal phenotype and in silico analysis results, we concluded that this novel β-globin gene mutation was associated with the mild phenotype of β-thal.